(3GdSjGSGJ GdEbJUGOjI hGdJLGQjI aj GdHdOGf GdYQHjI (B:s (3GdJcGed hGdJTZjd hGdMO ef GdabQ (B/s - (3GdNaja, eMehOs; (3QGO, SMQ JbOjSjs; (3GdCbQY, eYJUe s ((3HjQhJ(B: s (3GdeDSSI GdYQHjI ddOQGSGJ hGdfTQ(B, s, 2012)
(3JYRjR GdSjGSGJ GdEbJUGOjI hGdJLGQjI GdehLgI ddfeh Ydi GdeSJhi GdEbdjej(B- (3HMK GdYdGbI Hjf GdJLGQI hGdabQ MGdI eUQ(B- (3JCKjQ SjGSGJ GdJLGQI hGdESJKeGQ Ydi GdJTZjd hGdabQ aj GdCQOf(B- (3YedjI GdJMQjQ GdEbJUGOj hGdJLGQj aj GdeZQH hBKGQgG(B- (3hVY SjGSGJ GdEbJUGO Gdcdj hGdJLGQI JMJ GdEMJdGd aj GdGQV GdadSWjfjI(B- (3GdSjGSI GdJLGQjI hGdEfOeGL GdEbdjej hGdfeh GdOGYe ddabQGA(B- (3GdJLGQI GdYQHjI GdHjGfGJ hGdfeGPL hGdbVGjG(B- (3GSJQGJjLjI JfehjI ddMO ef GdabQ hGdJcGed GdYQHjs
(3GdedGMb U(B.393s
Keywords: (3GdHdOGf GdYQHjIs; (3GdSjGSI GdEbJUGOjIs; (3GdSjGSI GdJLGQjIs